2019
DOI: 10.1016/j.annemergmed.2019.08.175
|View full text |Cite
|
Sign up to set email alerts
|

169 Palliative Consultations from the Emergency Department Reduce Inpatient Length of Stay and Costs

Abstract: evaluated the curriculum using a standardized assessment and review tool. In phase IV, the detailed feedback was used to refine the curriculum further.Results: Phases I to III have been completed. Phase IV will be completed in late 2019. The draft curriculum has 8 non-clinical sections and 10 clinical sections: (1) Introduction to the Human Body; (2) Patient Assessment; (3) Resuscitation; (4) Trauma; (5) Medical Emergencies (6) Pediatrics; (7) Obstetrics and Neonatal Care; (8) Toxicological and Environmental E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…For the impact of PC interventions on LOS, a pooled meta-analysis was not possible as the majority of studies assessing LOS did not report any measures of variance for the intervention or control groups. 10,[17][18][19][20] Furthermore, the three studies that did report measures of variance each utilized a different study design, further limiting the ability to pool. 8,9,11 Finally, the units of time used across the studies varied between minutes and days.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…For the impact of PC interventions on LOS, a pooled meta-analysis was not possible as the majority of studies assessing LOS did not report any measures of variance for the intervention or control groups. 10,[17][18][19][20] Furthermore, the three studies that did report measures of variance each utilized a different study design, further limiting the ability to pool. 8,9,11 Finally, the units of time used across the studies varied between minutes and days.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…21,22 In some cases, the 95% CI for the RoM of a particular study could not be calculated due to insufficient information provided by the study authors. 10,[18][19][20] The 95% CI was estimated in one study that did not report standard deviation but reported the p-value. 17 Due to methodological and clinical heterogeneity, pooling of the RoMs was not completed.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 3 more Smart Citations